2021
DOI: 10.3389/fmolb.2021.754098
|View full text |Cite
|
Sign up to set email alerts
|

The Hepatoprotective Effect of Piperine Against Thioacetamide-Induced Liver Fibrosis in Mice: The Involvement of miR-17 and TGF-β/Smads Pathways

Abstract: Liver fibrosis is characterized by a series of events including activation of quiescent hepatic stellate cells (HSCs) into proinflammatory, contractile, and fibrogenic myofibroblasts, which is the primary trigger for the fibrogenesis process. HSC activation involves many signaling pathways such as the TGF-β/smads pathway. Specific microRNAs have been identified to play a crucial role in the activation of HSCs via various signaling pathways. Piperine has recently been studied as a promising anti-fibrotic agent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The detected increased plasma levels of miR-155 and miR-21 and their relation to TAA-toxicity are coincident with the results evaluated the role of another microRNA in TAA toxicity; where one study reported the presence of higher levels of microRNAs; 122, 192, and 194 in the experimental group has given TAA (Teksoy et al,2020). Further, other studies detected deregulated expression levels of MiR-17 and 378 due to TAA toxicity, and this induced hepatic fibrosis through activation of hepatic stellate cells via altering Wnt/βcatenin and TGF-β/smads pathways (Zaafan and Abdelhamid.,2022;Abdelhamid et al,2021).…”
Section: Figmentioning
confidence: 99%
“…The detected increased plasma levels of miR-155 and miR-21 and their relation to TAA-toxicity are coincident with the results evaluated the role of another microRNA in TAA toxicity; where one study reported the presence of higher levels of microRNAs; 122, 192, and 194 in the experimental group has given TAA (Teksoy et al,2020). Further, other studies detected deregulated expression levels of MiR-17 and 378 due to TAA toxicity, and this induced hepatic fibrosis through activation of hepatic stellate cells via altering Wnt/βcatenin and TGF-β/smads pathways (Zaafan and Abdelhamid.,2022;Abdelhamid et al,2021).…”
Section: Figmentioning
confidence: 99%
“…(11) Targets the FXR-miR-29a signaling pathway in HSC: Sweroside [235] . (12) Improves HSC activation by inhibiting NLRP3 inflammatory vesicle activation: Dehydromevalonolactone [236] , Palmitic acid [237] . (13) Targeting FGF19/FGFR4 signaling to block LPS-induced HSC proliferation and activation: Salvianolic acid B [238] .…”
Section: Othersmentioning
confidence: 99%
“…Hence, modulation of miR-130b-5p may be a key curative maneuver to LF [11] . It has been demonstrated that upregulation of miRNA-17 expression and inhibition of smad-7 recovery are accompanied by significant activation of TGF-β/smads signaling, further promoting activated HSCs and collagen deposition in hepatocytes [12] . Mmu-miR-137-3p addresses Ppic directly as well as creates a modulatory axis with Ppic to regulate HSCs stimulation in TGF-β-induced mice [13] .…”
Section: Introductionmentioning
confidence: 99%
“…The low bioavailability of curcumin can be enhanced with the coadministration with piperine (Shoba et al, 1998), an alkaloid compound extracted from the seeds of Piper nigrum . Piperine alone has intrinsic anti‐oxidant, anti‐inflammatory and hepatoprotective effects (Abdelhamid, Selim, & Zaafan, 2021; Derosa, Maffioli, & Sahebkar, 2016).…”
Section: Introductionmentioning
confidence: 99%